Accidental Archaeologists : true stories of unexpected discoveries - Albee, Sarah; Hackett, Nathan (New York : Scholastic Press, 2020)
"A lighthearted but informative look at chance discoveries made by ordinary people, of artifacts (and treasures) from the past. Many of these discoveries have led to leaps in our knowledge of history and science. Each short chapter will begin with a dramatic story of discovery, followed by the significance of the artifact that was discovered, followed by a look into the history of the civilization/era from which the artifact originates. The stories will show readers that potentially anyone-construction workers, farmers, casual passers-by, and even kids-can make discoveries like these"--.
Introduction: A bunch of amateurs -- A blast from the past -- Etched in stone -- A giant in the field -- In a pile, crocodile -- What a wreck -- Proving a point -- Paleo painters -- The case of the copper coins -- Scroll up -- Bogged down -- Lucky break -- Eternally yours -- Temple of gloom -- Grave considerations -- Dead in a ditch -- Skeleton key -- The chamber of secrets -- You don't say -- A little more dirt on archaeology -- How to be an amateur archaeologist: expect the unexpected.
new kids book 2024 spring.
Includes bibliographical references (pages 194-200).
Ages 8-12.
Keywords: Archaeology -- History -- Juvenile literature; Discoveries in science -- History -- Juvenile literature; Archaeologists -- Juvenile literature